The Effect of Carbon Emission Disclosure and Tax Avoidance on Firm Value: The Moderating Role of Board Diversity - Wijaya Triwacananingrum; Jemmima Rachmadita; Rayhan Mahatma Harikusuma (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
This study examines how board diversity affects the link between a company's carbon emission disclosure, tax avoidance, and its market value. Using data from 31 non-financial companies on Indonesia's Kompas 100 index from 2020 to 2023, the research found that carbon disclosure, tax avoidance, and board diversity do not directly influence firm value on their own. However, the study reveals that board diversity plays a crucial moderating role. It significantly strengthens the positive link between carbon emission disclosure and firm value, making environmental transparency more valuable to investors. In contrast, it does not affect the relationship between tax avoidance and firm value. The research suggests that for Indonesian companies, implementing board diversity is a key strategy to enhance the impact of their sustainability reporting. Furthermore, diverse boards can promote more ethical tax practices, which may positively influence company value in the long run.